To Enhance Non-English Major Students’ English Communicative Competence by Improving Students’ English Learner Autonomy through Organization Development Interventions —An Action Research at Zhejiang Yuexiu University of Foreign Languages (ZYUFL) in China - Li, Ling; Kim, Seongdok (ABAC ODI JOURNAL Vision. Action. Outcome, 2020)
The research paper analyzed the impact of organization development interventions (ODI) on learner autonomy (LA) and communicative competence (CC) of non-English major students in ZYUFL, Zhejiang, China. The main objectives were to determine the differences of students’ learner autonomy and communicative competence between the pre- and post-ODI phases and to investigate the impact of students’ learner autonomy on communicative competence after ODIs. Based on the preliminary diagnosis and pre-ODI results, the researcher conducted purposeful ODIs (three action learning cycles including coaching, goal setting, team building, dialogue and Appreciative Inquiry), but remained the same in the control group. The post-ODI results showed significant improvement on learner autonomy and communicative competence in the experimental group but stayed almost in the same level in the control group. According to the results of paired sample t-test, there were significant differences between pre- and post-ODI results in learner autonomy and communicative competence. Based on the Simple Linear Regression results, learner autonomy had a positive significant impact on communicative competence. The analysis of the qualitative data (three learning journals, one reflective statement and two post-ODI meetings) triangulated the results.